"Not everyone gets the opportunity to experience this": Swedish elite athletes` perceptions of quality of life - Lundqvist, C.; Träff, M.; Brady, A. (International Journal of Sport Psychology, 2021)
This study explored theessence of Swedish elite athletes` experiences of their quality of life (QOL). Eight individual elite sports athletes (3 men and 5 women; mean age 25.5 years, range: 20-32 years) were interviewed twice. Using interpretative phenomenological analysis, findings showed the essence of QOL to consist of four categories.Category 1: An inner striving to move forward in athletic development. Category 2: Perceived gratitude for the opportunity to invest in the sport and value-driven behaviors. Category 3: Good prerequisites for sport investment (satisfaction with opportunities for goal achievement, having a goal directed plan, and perceived relief from stressors). Category 4: Emotional states which encompassed durable and transientemotionslinked to training, performing and goal achievement. Discussion is presented regarding the importance of future research and applied sport psychology practice considering elite athletes` holistic subjective experiences in context to better understand well-being, mental health and QOL for this population.